Structural, surface morphological and dielectric studies of guanidinium salt incorporated poly (ethylene oxide)/poly (vinyl pyrrolidone) solid polymer electrolytes - R. Pradeep; V. Siva; M. Anandha Jothi; A. Murugan; A. Shameem; S. Sanjana; E. Hemnath; Abdullah G Al-Sehemi (Heliyon, 2024)
The research article investigates the effect of incorporating the guanidinium carbonate (GuC) salt into the poly vinylpyrrolidone (PVP) and polyethylene oxide (PEO) polymer matrix. Various weight percentages of GuC enriched PVP/PEO solid polymer electrolytes (SPEs) have been prepared by the simplest solution casting process. XRD analysis revealed that the incorporation of the GuC salt led to changes in the crystalline structure of the PVP/PEO. FTIR analysis confirms the presence of guanidinium carbonate in the blended polymeric system. FESEM imaging showed the uniform and smooth surface view of the electrolytes. DSC analysis suggests that the addition of the GuC led to a decrease in the melting temperature and an increase in the crystallisation temperature. The temperature-dependent dielectric analysis showed that the presence of the organic salt led to an increase in the dielectric constant of the polymer blend. Among all the prepared electrolytes, 25 wt.% GuC added polymer electrolyte achieved a higher conductivity of 3.00764 × 10−7 S/cm. Overall, the results of the study suggest that the incorporation of the GuC salt into the PVP/PEO can lead to significant changes in the structural, thermal, and dielectric properties of the blend. These findings have potential implications for the use of PVP/PEO blends in solid state battery applications.